Efficacy of NS5A inhibitors against unusual and potentially difficult-to-treat HCV subtypes commonly found in sub Saharan Africa and South East Asia - Nguyen, D; Smith, D; Vaughan-Jackson, A; Magri, A; Barnes, E; Simmonds, P; STOP-HCV Consortium (Elsevier, 2020)
Background Aims: The efficacy of NS5A inhibitors against several less common subtypes of hepatitis C virus (HCV) is poorly characterised. Some subtypes including 3b, 3g, 6u and 6v commonly harbour amino acid residues as wild type in NS5A that may confer resistance to direct acting antivirals (DAAs) in other common subtypes. Data from patients also suggest that 1l and 4r with amino acid substitutions at positions 28-31 and 93 in NS5A are relatively resistant to DAA therapy.